2002
DOI: 10.1002/1521-396x(200202)189:2<599::aid-pssa599>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Applied Mechanical Stressses on the Impedance Response in Amorphous Microwires with Vanishing Magnetostriction

Abstract: The effect of external (torsion and tensile) stresses on the electrical impedance of nearly-zero magnetostrictive amorphous microwires (conventional and glass covered) is reported. Glass coated Co 68.5 Mn 6.5 Si 10 B 15 microwire exhibits a maximum relative change in magnetoimpedance ratio up to around 130% at a frequency of 10 MHz, magnetic dc field of about 180 A/m and under tension of 60 MPa. This giant magnetoimpedance (GMI) effect of the microwire is affected by the magnetoelastic anisotropy induced in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
1
Order By: Relevance
“…As to the as-cast wires, the distribution of residual stress is inhomogeneous, which induces inhomogeneous anisotropy field. Any fluctuation in local magnetic anisotropy may change the orientation of the easy magnetization axis and substantially deteriorate the GMI magnitude [19][20]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As to the as-cast wires, the distribution of residual stress is inhomogeneous, which induces inhomogeneous anisotropy field. Any fluctuation in local magnetic anisotropy may change the orientation of the easy magnetization axis and substantially deteriorate the GMI magnitude [19][20]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…But the effect of tensile stress on Co-based amorphous ribbons despite of the outstanding impedance responses and the acceptable field sensitivity has been given little attentions. Gonzalez et al [13] found that the MIR in glass-covered Co-rich wires was little increased when axial tensile stress less than 100 MPa was applied, but its improvement was not significant, and a maximum value as high as 130 % at 10 MHz was observed when the tension was about 60 MPa [14]. It is known that application of an external tensile stress increases the inner core domains under stress-induced magnetoelastic field, develops an axial anisotropy, and hence reduces the MI effect [15].…”
Section: Introductionmentioning
confidence: 99%
“…Outro parâmetro que tem sido considerado para estudar a dependência da resposta GMI com o campo magnético externo é a aplicação de tensão mecânica na amostra. Por exemplo, num microfio amorfo de composição Co 68.5 Mn 6.5 Si 10 B 15 (com magnetostrição negativa e próxima a zero), com uma corrente de frequência de 10 MHz [77], aplicou-se uma tensão de 60 MPa obtendo-se um máximo de GMI de 130%, para um campo magnético de 180 A/m. Com a aplicação da tensão mecânica, foi induzida uma anisotropia transversal, que ajuda ao aumento da razão GMI.…”
Section: Corrente Diminui Pelo Efeito Pele Corrente Aumenta Pelo Efei...unclassified